A Sub‐Diffraction‐Limit Dimension All‐Plasmonic Optical Memory Using Non‐Linear Photochromism - Shuichi Toyouchi; Mathias Wolf; Kenji Hirai; Yasuhiko Fujita; Tomoko Inose; Beatrice Fortuni; Eduard Fron; Johan Hofkens; Steven De Feyter; James Hutchison; Tsuyoshi Fukaminato; Hiroshi Uji‐i (Advanced Science)
Abstract The development of compact, high‐speed, and energy‐efficient optical memories remains a significant challenge in photonic and plasmonic technologies. Conventional optical memories are inherently limited by light diffraction, restricting miniaturization and causing inefficient energy transfer. A promising strategy to overcome these limitations is using propagating surface plasmon polaritons (SPPs), enabling the confinement and propagation of optical fields along metal interfaces, and allowing photonic devices to scale down to sub‐diffraction‐limit dimensions. This work presents an all‐plasmonic optical memory system based on silver nanowires (AgNWs) coated with photochromic diarylethene (DAE). By utilizing SPPs, reversible Write/Erase functions are achieved through multiphoton excitation, modulating the photostationary state of DAE. The refractive index changes regulate SPP propagation efficiency along the AgNW, with the memory state being read via plasmonic second‐harmonic generation. The synergy between nonlinear plasmonics in AgNWs and the photochromic properties of DAE enables complete memory operations, including writing, erasing, and reading ON/OFF states. This sub‐diffraction‐limit system paves the way for ultra‐compact, molecular‐scale optical memory devices.